To What Extent Does the Involvement Load Hypothesis Predict Incidental L2 Vocabulary Learning? A Meta‐Analysis. Issue 2 (14th January 2021) - Yanagisawa, Akifumi; Webb, Stuart
Abstract: The involvement load hypothesis (ILH) was designed to predict the effectiveness of instructional tasks for incidental L2 vocabulary learning. In this meta‐analysis we examined 398 effect sizes from 42 empirical studies ( N = 4, 628) to explore (a) the overall predictive ability of the ILH, (b) the relative effects of different components of the ILH (need, search, and evaluation), and (c) the influence of potential factors moderating learning (e.g., time on task, frequency of encounters or use, and test format). Results showed that the ILH was significantly predictive of learning and explained 15.0% and 5.1% of the variance in effect sizes on immediate and delayed posttests, respectively. We found that the evaluation component contributed to the greatest amount of learning, followed by need, whereas search did not contribute to learning. Moderator analyses revealed that (a) test format and frequency moderated learning gains and (b) involvement load had a greater impact on learning than time on task. Abstract :